Interfacial Trap‐Assisted Triplet Generation in Lead Halide Perovskite Sensitized Solid‐State Upconversion. Issue 27 (28th May 2021) - Wang, Lili; Yoo, Jason J.; Lin, Ting‐An; Perkinson, Collin F.; Lu, Yongli; Baldo, Marc A.; Bawendi, Moungi G.
Abstract: Photon upconversion via triplet–triplet annihilation (TTA) has promise for overcoming the Shockley–Queisser limit for single‐junction solar cells by allowing the utilization of sub‐bandgap photons. Recently, bulk perovskites have been employed as sensitizers in solid‐state upconversion devices to circumvent poor exciton diffusion in previous nanocrystal (NC)‐sensitized devices. However, an in‐depth understanding of the underlying photophysics of perovskite‐sensitized triplet generation is still lacking due to the difficulty of precisely controlling interfacial properties of fully solution‐processed devices. In this study, interfacial properties of upconversion devices are adjusted by a mild surface solvent treatment, specifically altering perovskite surface properties without perturbing the bulk perovskite. Thermal evaporation of the annihilator precludes further solvent contamination. Counterintuitively, devices with more interfacial traps show brighter upconversion. Approximately an order of magnitude difference in upconversion brightness is observed across different interfacial solvent treatments. Sequential charge transfer and interfacial trap‐assisted triplet sensitization are demonstrated by comparing upconversion performance, transient photoluminescence dynamics, and magnetic field dependence of the devices. Incomplete triplet conversion from transferred charges and consequent triplet‐charge annihilation (TCA) are also observed. The observations highlight the importance of interfacial control and provide guidance for further design and optimization of upconversion devices using perovskites or other semiconductors as sensitizers. Abstract : The effect of interfacial properties on charge‐initiated triplet sensitization in perovskite‐sensitized solid‐state upconversion devices is investigated. Trap‐assisted triplet sensitization is demonstrated via modification of interfacial trap densities of the devices through surface treatment while monitoring the upconversion performance. Devices with more interfacial traps show brighter upconversion, highlighting the importance of interfacial control in perovskite‐sensitized upconversion devices.